A comparative analysis of the role of Interplanetary Magnetic Field (IMF) and Sudden Impulse (SI) in triggering a Substorm - Sinha, Shipra; Vichare, Geeta; Sinha, A.K. (My University, 2022)
During a typical Akasofu-type of substorm, the southward component of IMF Bz is necessary prior to the onset. However, a sudden compression of solar wind, if intense enough, can also sometimes trigger a substorm, and is independent of the IMF orientation. The Akasofu-type substorm and the Impulse-induced substorm may differ in their occurrence mechanism and ground-based observations. This is shown using the initial four substorm events discussed in this paper having distinctly different IMF and sudden impulse conditions. A question then arises is how will these signatures vary when both sudden impulse and a southward component of IMF Bz are present prior to the onset. To account for the same, we analyze two substorm events of 05th April 2010 and 22nd June 2015. The substorm onsets on these days not just coincided with the sudden impulse but also a southward component of IMF Bz was present prior to the onsets. The present study accounts for the similarities and differences among isolated IMF induced substorms, isolated impulseinduced substorms and when both sudden impulse and a southward component of IMF Bz are present. We examined the relative dominance between the two factors in triggering a substorm using ground-based and satellite-based observations. If IMF Bz is near zero, a strong pressure pulse and/or large IMF By can lead to particle precipitation away from the usual midnight. To further ensure whether a pressure pulse or IMF By predominantly influences the substorm onset location, a statistical analysis of isolated substorms will be needed.
Keywords: Magnetospheric Substorms; Interplanetary Shocks; High-Latitude Dynamics